Stabilization of DC–DC buck converter with unknown constant power load via passivity‐based control plus proportion‐integration - Wei He (Wiley, 2021)
Abstract It is known that constant power load (CPL) may cause a negative impedance, which seriously affects the stability of power system. In this paper, a new control algorithm for DC–DC buck converter feeding unknown CPL is proposed. First, under the assumption of known extracted power load, the standard passivity–based control (PBC) is presented to reshape the system energy and compensate for the negative impedance and a proportion‐integration (PI) action around passive output is added to improve disturbance rejection performance, which forms the PBC plus PI (PBC+PI). Then, a parameter estimation algorithm is developed, based on immersion and invariance (I&I) technique, in order to online estimate the extracted power load. In the next step, the online estimation scheme is adopted to construct an adaptive strategy. Finally, the stability analysis of the cascaded system containing a closed‐loop control system and observer error dynamics is conducted. Simulation and experimental results are demonstrated to validate the performance of the proposed controller.